Topological Study of Zeolite Socony Mobil-5 via Degree-Based Topological Indices - Nouman Saeed; Kai Long; Tanweer Ul Islam; Zeeshan Saleem Mufti; Ayesha Abbas (Journal of Chemistry)
Graph theory is a subdivision of discrete mathematics. In graph theory, a graph is made up of vertices connected through edges. Topological indices are numerical parameters or descriptors of graph. Topological index tells the symmetry of compound and helps us to compare those mathematical values, with boiling point, melting point, density, viscosity, hydrophobic surface area, polarity, etc., of that compound. In the present research paper, degree-based topological indices of Zeolite Socony Mobil-5 are calculated. Names of those topological indices are Randić index, first Zagreb index, general sum connectivity index, hyper-Zagreb index, geometric index, ABC index, etc.